Increased rotational flow in the proximal aortic arch is associated with its dilation in bicuspid aortic valve disease. (28th March 2019) - Dux-Santoy, Lydia; Guala, Andrea; Teixidó-Turà, Gisela; Ruiz-Muñoz, Aroa; Maldonado, Giuliana; Villalva, Nicolás; Galian, Laura; Valente, Filipa; Gutiérrez, Laura; González-Alujas, Teresa; Sao-Avilés, Augusto; Johnson, Kevin M; et al.
Abstract: Aims: Aortic dilation in bicuspid aortic valve (BAV) might extend to the proximal arch. Arch flow dynamics and their relationship with this segment dilation are still unexplored. Using 4D-flow cardiovascular magnetic resonance, we analysed flow dynamics in the arch for each BAV morphotype and their association with this segment dilation. Methods and results: One hundred and eleven BAV patients (aortic diameters ≤55 mm, non-severe valvular disease), 21 age-matched tricuspid aortic valve (TAV) patients with dilated arch and 24 healthy volunteers (HV) underwent 4D-flow. BAV were classified per fusion morphotype: 75% right-left (RL-BAV), and per arch dilation: 57% dilated, mainly affecting the right-noncoronary (RN) BAV (86% dilated vs. 47% in RL-BAV). Peak velocity, jet angle, normalized displacement, in-plane rotational flow (IRF), wall shear stress, and systolic flow reversal ratio (SFRR) were calculated along the thoracic aorta. ANCOVA and multivariate linear regression analyses were used to identify correlates of arch dilation. BAV had higher rotational flow and eccentricity than TAV in the proximal arch. Dilated compared with non-dilated BAV had higher IRF being more pronounced in the RN-morphotype. RN-BAV, IRF, and SFRR were independently associated with arch dilation. Aortic stenosis and male sex were independently associated with arch dilation in RL-BAV. Flow parameters associated with dilation converged to the values found in HV in the distal arch. Conclusion: Increased rotational flow could explain dilation of the proximal arch in RN-BAV and in RL-BAV patients of male sex and with valvular stenosis. These patients may benefit from a closer follow-up with cardiac magnetic resonance or computed tomography.